Makna Allah Pencipta Manusia dan Problematika Arti Kata ‘Kita’ dalam Kejadian 1:26-27 - Juliman Harefa (EPIGRAPHE: Jurnal Teologi dan Pelayanan Kristiani, 2019)
This paper is an exegetical study of the book of Genesis 1:26-27, to understand whom God created, why God created a man who is called a noble creature, and studies the meaning of being pictured and similar to God. The study uses the hermeneutic spiral method (from text to context) to reveals the meaning of the original text of the Bible. Also, the implementation of the meaning of the original text today. The study of the text of the word Elohim, Yahweh/Adonay, and We contains the notions of the purity, omnipotence, majesty, and glory of the creator of the universe. The creator God created humans in His image and likeness so that humans have "divine potential" that is not possessed by other creatures. The divine potential is the human self-image that has a soul that will understand as the quality of human resources themselves, namely the potential for spirituality, ratios, wills that will apply in the secular, cultural, and educational world in this millennial era.  AbstrakArtkel ini merupakan studi eksegetis kitab Kejadian 1:26-27, untuk memahami tentang siapa Allah pencipta, mengapa Allah menciptakan manusia yang disebut sebagai makhluk mulia dan mengkaji makna segam-bar dan serupa dengan Allah. Kajian ini menggunakan metode herme-neutik spiral (dari teks kepada konteks) yaitu studi eksegetis yang mengungkap makna teks asli Alkitab dan implementasi makna teks asli pada masa kini. Kajian teks kata Elohim, Yahwe/Adonay dan Kita mengandung arti kemahasucian, kemahakuasaan, keagungan dan kemulia-an Sang Pencipta alam semesta. Allah Pencipta menciptakan manusia me-nurut gambar dan rupa-Nya, sehingga manusia memiliki “potensi ilahi” yang tidak dimiliki oleh makhluk lain yang diciptakan oleh Allah. Potensi ilahi adalah citra diri manusia yang memiliki jiwa akan dipahami sebagai kualitas sumberdaya manusia itu sendiri yakni potensi spiritualitas, rasio, kehendak yang akan diaplikasikan dalam dunia sekuler, budaya dan pendidikan di era milenial.